Factors influencing lithium versus valproate prescription preference in the maintenance treatment of bipolar patients: a report from the Italian Early Career Psychiatrists (SOPSI-GG). (1st March 2021) - Buoli, Massimiliano; Gattoni, Eleonora; Collantoni, Enrico; Monteleone, Alessio Maria; Solmi, Marco; Longo, Luisa; Ribolsi, Michele; Santambrogio, Jacopo; Bersani, Francesco Saverio; Aguglia, Andrea; Serafini, Gianluca; Signorelli, Maria Salvina; et al.
Abstract: Background: Objective of the present manuscript is to investigate, among Italian early career psychiatrists (ECPs), prescriber and patient-related factors associated with lithium or valproate preference to treat patients affected by Bipolar Disorder (BD). Methods: An on-line survey was carried out among 252 ECPs, investigating their prescription patterns in relation to lithium and the differences with prescription of valproate. Collected data were compared according to lithium or valproate prescription preference in the long-term treatment of BD by χ 2 tests for qualitative variables. Results: Over two thirds of ECPs preferred lithium over valproate for the maintenance treatment of BD. Less than half of the sample used lithium as first-line agent for mania or major depression, and less than one third for mixed episodes. Factors associated with lithium preference as first-line maintenance treatment include perception of having a good knowledge of lithium ( p  < 0.001) and complete satisfaction with education on lithium ( p  < 0.001). One of the main factors to prefer valproate was the concern about long-term side effects of lithium ( p  < 0.001). Conclusions: Type of education, source of information, clinical experience and safety concerns influence the choice of lithium versus valproate in the long-term treatment of BD. Present findings may guide educational training of ECPs. KEY POINTS: Lithium has been less prescribed in the last years for long-term treatment of Bipolar Disorder. Educational and clinical factors seem to influence the attitude to prescribe lithium. Only half of the Italian early career psychiatrists declare to have at least an adequate knowledge of lithium. Residency program in psychiatry should consider the implementation of education on lithium.